2020
DOI: 10.3389/fendo.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Inhibits the Expression of CFSH in Mud Crab

Abstract: Crustacean female sex hormone (CFSH) is a key regulator of crustacean sex differentiation. The expression of Sp-CFSH in the mud crab Scylla paramamosain showed a tissue-specific and gender-variant pattern. To explore the role of DNA methylation in Sp-CFSH expression, the 5 ′-flanking region of Sp-CFSH was cloned, and one CpG island containing 12 CpG sites was found. Results of sodium bisulfite sequencing and methylated DNA immunoprecipitation showed that CpG island methylation was stable in the eyestalk gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…Given these intersex crabs are genetic females, the masculinized phenotype may be related to the lowered EsCFSH-1 expression and the increased EsIAG expression, which eventually lead to the unorthodox emergence of AG. Furthermore, as the demethylation of 5′-UTR region of CFSH ensured the high expression of CFSH in the female EG ( Jiang et al, 2020a ), our ongoing study will find out whether an abnormally high methylation of this region decrease the expression of EsCFSH-1 in the intersex crabs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given these intersex crabs are genetic females, the masculinized phenotype may be related to the lowered EsCFSH-1 expression and the increased EsIAG expression, which eventually lead to the unorthodox emergence of AG. Furthermore, as the demethylation of 5′-UTR region of CFSH ensured the high expression of CFSH in the female EG ( Jiang et al, 2020a ), our ongoing study will find out whether an abnormally high methylation of this region decrease the expression of EsCFSH-1 in the intersex crabs.…”
Section: Discussionmentioning
confidence: 98%
“…CFSH has been regarded as an upstream regulator of IAG, while the recent evidence supported the possible existence of a negative regulatory loop between CFSH and IAG. Previous studies found that CFSH of Scylla paramamosain could inhibit the expression of IAG in vitro (Liu et al, 2018) and the inhibitory mechanism was later detailed explained (Jiang et al, 2020a;Jiang et al, 2020c), while IAG1 and CFSH of Lysmata vittata was able to inhibit the expression of each other reciprocally (Liu et al, 2021b;Liu et al, 2021c). However, the research of the hormone control on sex determination and differentiation has been limited for lacking of sex identification during the embryogenesis and larval development.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, promoter methylation has also been demonstrated in the tunicate Ciona intestinalis , a representative of the phylogenetically most basal group of the Chordata, [ 96 ] suggesting that gene regulation by promoter methylation predates vertebrates. Promoter methylation has also been demonstrated in CpG islands of mud crab, Scylla paramamosain , a representative of the arthropods, and was functionally associated with gene activity (Figure 5B) [ 100 ] suggesting that gene regulation via promoter methylation is more widespread in the animal kingdom. Even the prebilaterian sponge Amphimedon queenslandica exhibits sharp mC depletion at promoters, [ 55 ] a feature that was previously exclusively attributed to vertebrates, suggesting that the involvement of promoter methylation in gene regulation may be traced back to the early steps of animal evolution.…”
Section: Functional Differences Of Dna Methylation Between Vertebrate...mentioning
confidence: 99%
“…CpG hypermethylation in the island contributes to gene silencing, resulting in expression of the male phenotype. Reproduced from [ 100 ] with permission. (C) Intense methylation of repetitive elements in zebrafish, Danio rerio , versus very low methylation of repetitive elements in honeybee, Apis mellifera , in a generally hypomethylated background.…”
Section: Functional Differences Of Dna Methylation Between Vertebrate...mentioning
confidence: 99%
“…194,195 In addition, DNA methylation and many histone modifications have been identified in a number of crustaceans, including shrimp and crabs. [196][197][198] In summary, more efforts are needed to promote the application of pan-genomics, 3D genomics, and epigenomics to crustacean research. The application of genomic resources in the genetic breeding of farmed crustaceans is mainly concentrated on shrimp and crabs.…”
Section: Utilization Of Multiple Novel Genomic Approaches In Crustace...mentioning
confidence: 99%